2015
DOI: 10.1002/biof.1236
|View full text |Cite
|
Sign up to set email alerts
|

Disease chemopreventive effects and molecular mechanisms of hydroxylated polymethoxyflavones

Abstract: Recent increasing attention in research of polymethoxyflavones (PMFs) from Citrus genus because of their wide range of biological properties has been reported in various studies. Hydroxylated PMFs are unique flavones and recognized as the methoxy group of PMFs that is substituted for hydroxyl one. Hydroxylated PMFs are naturally existed in citrus peel and other plants as well as occurred as metabolites of their PMFs counterparts. Several in vitro and in vivo studies have documented the chemopreventive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 98 publications
1
31
0
Order By: Relevance
“…In addition to substituting the hydrogen atoms on A, B and C rings of flavone skeleton, the hydroxy groups may also replace the methoxy groups to form the hydroxylated PMFs. The major citrus hydroxylated PMFs identified thus far are 5-demethyl PMFs, commonly generated in aged citrus pericarp as well as citrus fruits undergoing prolonged storage, formed through autohydrolysis of their PMF counterparts (Lai et al, 2015). It is surprisingly to find out that 5-demethyl PMFs may possess superior inhibitory effect on inflammation-induced tumorigenesis than their parent polymethoxylated PMFs (Ma et al, 2014), probably resulting from the better permeability and membrane penetrating activity of the mono-or di-hydroxylated PMFs, leading to their better absorption rate and bioavailability (Wang, Li and Ho, 2018).…”
Section: Chemistry Of Citrus Peel Pmfsmentioning
confidence: 99%
“…In addition to substituting the hydrogen atoms on A, B and C rings of flavone skeleton, the hydroxy groups may also replace the methoxy groups to form the hydroxylated PMFs. The major citrus hydroxylated PMFs identified thus far are 5-demethyl PMFs, commonly generated in aged citrus pericarp as well as citrus fruits undergoing prolonged storage, formed through autohydrolysis of their PMF counterparts (Lai et al, 2015). It is surprisingly to find out that 5-demethyl PMFs may possess superior inhibitory effect on inflammation-induced tumorigenesis than their parent polymethoxylated PMFs (Ma et al, 2014), probably resulting from the better permeability and membrane penetrating activity of the mono-or di-hydroxylated PMFs, leading to their better absorption rate and bioavailability (Wang, Li and Ho, 2018).…”
Section: Chemistry Of Citrus Peel Pmfsmentioning
confidence: 99%
“…Our studies have shown significant anti-inflammatory effects of flavonoid-enriched orange peel extracts as validated in cell-based and in vivo models for inflammation (Gosslau et al, 2014;Gosslau et al, 2011;Gosslau et al, 2018;Lai et al, 2015;Li et al, 2007;Sergeev et al, 2007;Wang et al, 2016). Chronic inflammation is also a key pathologic link between obesity and type 2 diabetes (T2D).…”
Section: Therapeutic Effects Of Citrus Fruit Polyphenolic Flavonoids mentioning
confidence: 76%
“…Since then, many more flavonoids were identified and characterized as bioactive compounds in peels and juice of citrus fruits (Gattuso et al, 2007;Meiyanto et al, 2012;Nair et al, 2018;Nogata et al, 2006;Putnik et al, 2017). In citrus fruits, polyhydroxylated flavonoids (PHFs) and polymethoxylated flavonoids (PMFs) are considered as major bioactives (Barreca et al, 2017;Lai et al, 2015;Li et al, 2009;Zhao et al, 2018). It is generally believed that antioxidant and anti-inflammatory activities are the main underlying mechanisms for the health-promoting effects of PHFs and PMFs.…”
Section: Therapeutic Effects Of Citrus Fruit Polyphenolic Flavonoids mentioning
confidence: 99%
See 1 more Smart Citation
“…One side the hydroxyl groups of flavones have free radical scavenging activity, but extensive conjugation of free hydroxyl groups to flavones results in low oral bioavailability; hence, they undergo rapid sulfation and glucuronidation in the small intestine and liver by phase II enzymes. Consequently, conjugated metabolites, but not the original compounds, can be found in plasma [34]. However, if one or more hydroxyl groups are capped by methylation, the substitution of a methoxy group by the hydroxyl group induces an increase in metabolic stability and improves transport and absorption.…”
Section: Discussionmentioning
confidence: 99%